Quantitative Wood Anatomy and Maximum Latewood Density from Yamal peninsula ... - Klesse, Stefan; Björklund, Jesper; Fonti, Marina; Nievergelt, Daniel; von Arx, Georg; Hantemirov, Rashit M.; Kukarskih, Vladimir V.; Garbrecht Thygesen, Lisbeth; Bjerregaard Pedersen, Nanna; Fonti, Patrick (EnviDat, 2024)
Data (Quantitative Wood Anatomy, Maximum Latewood Density, Volumetric Density, holo-cellulose-to-wood-ratio) used in the manuscript "New Prospects for Temperature Reconstructions from Relict Wood Using Tree-Ring Anatomy". Wood samples stem from Larix sibirica collected in the Yamal region, northeastern Siberia, Russia. We investigated wood properties of living trees and subfossil wood buried in riverbank sediments, dated to approximately -2760 to -2600 BCE. Our goal was to evaluate the integrity of climate proxies in sub-fossil wood and develop practical methods to detect wood degradation when reconstructing Late Holocene and Common Era climate conditions using tree-ring data. ... : Resource Title: Figure3_dataset.txt Size: 8581 bytes Format: text/plain URL: https://www.envidat.ch/dataset/743a897f-26e7-4871-a014-b0f95238564d/resource/2435516e-8dfc-4347-a35c-893eadcdf569/download/figure3_dataset.txt Description: This dataset contains the mean chronologies of MXD and QWA of the relict and living wood material presented in Figure 3. It also contains the JJA temperature record of the Salekhard Meteo station. ...